Copy number variation: New insights in genome diversity - Freeman, Jennifer L.; Perry, George H.; Feuk, Lars; Redon, Richard; McCarroll, Steven A.; Altshuler, David M.; Aburatani, Hiroyuki; Jones, Keith W.; Tyler-Smith, Chris; Hurles, Matthew E.; Carter, Nigel P.; Scherer, Stephen W.; et al. (Genome Research, 2006)
DNA copy number variation has long been associated with specific chromosomal rearrangements and genomic disorders, but its ubiquity in mammalian genomes was not fully realized until recently. Although our understanding of the extent of this variation is still developing, it seems likely that, at least in humans, copy number variants (CNVs) account for a substantial amount of genetic variation. Since many CNVs include genes that result in differential levels of gene expression, CNVs may account for a significant proportion of normal phenotypic variation. Current efforts are directed toward a more comprehensive cataloging and characterization of CNVs that will provide the basis for determining how genomic diversity impacts biological function, evolution, and common human diseases.
10.1101/gr.3677206